ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI IMPLEMENTASI ANGGARAN BERBASIS KINERJA - Kaillin Lalli Randa; Ida Ayu Purba Riani; Balthazar Kreuta (Universitas Cenderawasih, 2018)
The purpose of the study was to analyze what factors influence the Performance Based Budget by using a sample of 87 respondents working at the Secretariat of the Papuan People's Representative Council. While the data analysis technique used is the Ordinary least square (OLS) technique. The results of the study are indicated by the calculation of the mean (mean) of 32 item questions and 87 respondents and the result is 137.31. If the value is compared to the criteria that the author has set, then the average value is included in the